2020
DOI: 10.1038/s41598-020-58098-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Ai Chi for balance in individuals with chronic stroke: a randomized controlled trial

Abstract: This study investigated the effectiveness of Ai Chi compared to conventional water-based exercise on balance performance in individuals with chronic stroke. A total of 20 individuals with chronic stroke were randomly allocated to receive either Ai Chi or conventional water-based exercise for 60 min/time, 3 times/week, and a total of 6 weeks. Balance performance assessed by limit of stability (LOS) test and Berg balance scale (BBS). Fugl-Meyer assessment (FMA) and gait performance were documented for lower extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…There exists currently only one study 49 which compared the effects of different aquatic therapy methods (Table 3, Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There exists currently only one study 49 which compared the effects of different aquatic therapy methods (Table 3, Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…We found overall 22 trials ( N = 688), that test the potential of aquatic therapy on reduction of balance disability after stroke 23‐26,28,30,31,33‐40,42‐44,46‐49 . Thus, we included more studies than previous reviews and meta‐analyses, 7,8,10 which identified between four and eleven appropriate trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stroke causes an adequate decrease in quality of life even among those with no residual effects. 12,20 . Ideally, stroke treatment should improve patient's quality of life by reducing the long‐term consequences of the event.…”
Section: My Personal “Viewpoint”mentioning
confidence: 99%